This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **P ( M > m + n | M > m ) = (1-p ) m + n +1 (1-p ) m +1 = (1-p ) n 6 = (1-p ) n +1 = P ( M > n ) . 3.2.19 (a) λ ( t ) = lim h → 1 h · P ( t < T < t + h ) P ( T > t ) = lim h → R t + h t f ( x ) dx h · 1 1-F ( t ) = f ( t ) 1-F ( t ) . To get the last result, we were using the following theorem in Calculus: Theorem If f(t) is continuous at t, then lim h → R t + h t f ( x ) dx h = f ( t ) . (b) Using the ﬁnal result in (a) we can get λ ( t ) = λe-λt /e-λt = λ (c) λ ( t ) = 2 te-t 2 e-t 2 = 2 t...

View
Full
Document